Quantitative Assessment of Cefuroxime: A Second Generation Cephalosporin in Pharmaceutical Formulations and Spiked Plasma Using Ultra Performance Liquid Chromatography-Tandem Mass Spectrometry - Raza Siddiqui1, Masoom; Mohammad Wabaidur1, Saikh; A. Alothman1, Zeid; Ali Khan1, Moonis; Shamsul Ola2, Mohammad (Asian Journal of Chemistry, 2014)
A simple and rapid method has been developed for the determination of cefuroxime in pharmaceutical formulations and spiked plasma. The method involves the application of ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) for the quantitative assessment of cefuroxime. The chromatographic separation of the cefuroxime was carried out using BEH C18 column (100 mm × 2.1 mm, 1.7 μm particle size) using a binary mobile phase mixture of 1-octane sulfonic acid sodium salt (5.78 × 10-4 M) and acetonitrile (50:50, v/v) at a flow rate of 0.5 mL min-1. The UPLC-MS/MS have shorter analysis time of 1 min was found to be linear over the concentration range of 0.5-5 μg mL-1. Limit of detection and limit of quantitation of the UPLC-MS/MS method was obtained to be 0.10 and 0.301 μg mL-1. The method was validated as per the ICH guidelines. The recovery studies suggest an excellent recovery of the procedure which was found in the range of 99.94-100.47 % for the pharmaceutical formulation and 95.63 to 96.89 %. for the spiked plasma. The RSD range of the developed analytical procedure ranged from 0.90 %-1.68 % in intra-day studies and 1.42 %-1.97 %, respectively.